ONLINE ASSESSMENT OF COGNITIVE ASPECTS IN HIGHER EDUCATION - Fitriady, Gema; Sugiyanto, Sugiyanto; Sugiarto, Tatok (Gelanggang Pendidikan Jasmani Indonesia, 2020)
The use of online  assessment s has been widely used in various fields including universities. Research to find the validity of online  assessment s has been conducted and the results are high but the opinions of people who are assessed on the application of online  assessment s have not been carried out. The purpose of this study was to determine the opinion of the person being assessed after conducting an online  assessment . 150 students were selected to be respondents consisting of 126 male and 24 female who were taken by the sampling technique, namely the total sampling. The application of online  assessment s in universities is very suitable. There are several advantages to implementing online  assessment s, including 1) it is preferred by students so that students will be motivated to conduct assessment s; 2) high accessibility and flexibility; 3) rapid feedback. Therefore, the use of online  assessment s in higher education can be done without reducing the quality of the assessment .